2022
DOI: 10.1111/1440-1681.13632
|View full text |Cite
|
Sign up to set email alerts
|

A single bout of exhaustive treadmill exercise increased AMPK activation associated with enhanced autophagy in mice skeletal muscle

Abstract: Previous studies reported inconsistent findings on autophagy activation in skeletal muscles after acute exercise. In this study, we investigated the effect of a single bout of exhaustive treadmill exercise on AMPK and autophagy activations in mice gastrocnemius muscle in vivo. Male ICR/CD‐1 mice were randomly divided into the control and exercise groups. The later was subjected to a single bout of exhaustive treadmill exercise. Changes of AMPK, phosphorylation of AMPKThr172 (pAMPKThr172), and autophagy markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The main aim of the current review was to discuss the effects of polyamines and physical activity on musculoskeletal diseases. To the best of our knowledge, while few studies [ 160 , 170 ] reported that spermidine supplementation in mice models improves autophagy in aged or defected muscle, more numerous studies revealed that exercise intervention promotes the autophagy and mitophagy processes in the skeletal muscle through the regulation of muscle remodeling and homeostasis, and by promoting aged skeletal muscle repairing and hypertrophy [ 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main aim of the current review was to discuss the effects of polyamines and physical activity on musculoskeletal diseases. To the best of our knowledge, while few studies [ 160 , 170 ] reported that spermidine supplementation in mice models improves autophagy in aged or defected muscle, more numerous studies revealed that exercise intervention promotes the autophagy and mitophagy processes in the skeletal muscle through the regulation of muscle remodeling and homeostasis, and by promoting aged skeletal muscle repairing and hypertrophy [ 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, direct evidence was provided for skeletal muscle by Laker et al and Wang et al [ 54 , 59 ], who proved that exercise respectively induced mitophagy in C57BL/6J mice and autophagy in ICR/CD-1 mice, both conventional murine models, through AMPK signaling. In addition, in the same aged murine model (C57BL/6J), not only ULK1 was found to increase, but also Atg5, Atg7, and LC3-II when exercise was administrated [ 55 ].…”
Section: Effects Of Spermidine Supplementation and Exercise In Skelet...mentioning
confidence: 99%
See 1 more Smart Citation
“…Rodent studies assessing skeletal muscle adaptations have provided convincing evidence of an exercise-induced increase in autophagy initiation signaling, such as phosphorylation of ULK1 at S317 and S555 [43,44] and disruption of the BCL2-BECN1 inhibitory complex [22]. Moreover, a robust increase in markers of autophagosome content (e. g. [22,44,45]) and autophagy flux [22] following a single endurance exercise session in skeletal muscle is often reported in rodents [46][47][48], and is disrupted in mouse models of muscle dystrophy [49]. The increase in autophagosome content seems to be observed following at least 30 min of exercise [16,22] and to be independent of exercise intensity [44].…”
Section: Endurance Exercisementioning
confidence: 99%
“…The increase in autophagosome content seems to be observed following at least 30 min of exercise 16 22 and to be independent of exercise intensity 44 . The protein abundance of the autophagy receptor p62 has been shown to be decreased 22 44 45 or unchanged 46 50 51 following exercise in rodents. These findings have supported the widely accepted notion that endurance exercise increases autophagy in skeletal muscle.…”
Section: Current Insights Into Exercise and Training-induced Regulati...mentioning
confidence: 99%